Marine Tourism Promotion and Local Business Participation in Konawe Kepulauan: Qualitative Evidence - Sayyidah Nisa; Astati Astati; Muhammad Muslikun; Rustam Rustam (Journal of Innovative and Creativity (Joecy), 2026)
The study purpose was to analyze marine tourism promotion and local business participation in Konawe Kepulauan, Indonesia. This small-island regency has coastal and nature-based attractions, including Pantai Kampa and Air Terjun Tumburano, yet destination competitiveness remains shaped by promotion capacity, infrastructure readiness, and community participation. Materials and methods. This study used a descriptive qualitative approach based on interviews with key local-government agencies and documentary data on visitor flows, tourism retribution, and destination development. Results. The findings show that visitor arrivals increased from 5,060 in 2025 to 7,308 by May 2026, indicating that destination development and promotion have begun to improve market visibility. Local participation appears through Pokdarwis-supported destination management, parking services, food and beverage activities, gazebo rental, and emerging homestay initiatives. However, facilities, road access, sanitation, information boards, accommodation readiness, and structured digital promotion still require stronger institutional support. Conclusions. The study proposes a participatory tourism-business pathway in which digital promotion, community-based services, and small-scale local enterprises are integrated to strengthen sustainable marine tourism competitiveness.